Ebusiness technology kit for dummies - Allen, Kathleen R.; Weisner, Jon. (Foster City, Calif. IDG Books Worldwide, 2000)
Disc includes trial verisions of Microsoft Publisher and FrontPage 2000 and Microsoft Small Business video case studies
Title from title screen.
System requirements: Windows 95/98/NT 4.0, or Macintosh Power PC System 7.0 or above; 16 MB RAM; 4x CD-ROM drive; 640 x 480 pixel screen resolution; color monitor set to high color (16 bit); sound card, speakers; internet browser 3.0 or above.
Keywords: Electronic commerce; Small business -- Computer networks